2C.02: DO ARTERIAL HEMODYNAMIC PARAMETERS PREDICT COGNITIVE DECLINE OVER A PERIOD OF 2 YEARS IN SUBJECTS OLDER THAN 80 YEARS LIVING IN NURSING HOMES? THE PARTAGE STUDY. (June 2015) - Watfa, G.; Joly, L.; Kearny-Schwartz, A.; Labat, C.; Gautier, S.; Hanon, O.; Salvi, P.; Benetos, A.
Abstract : Objective: Several studies have highlighted a link between vascular alterations and cognitive decline. The PARTAGE study showed that arterial stiffness as evaluated by carotid-femoral pulse wave velocity (cfPWV) was associated with a more pronounced cognitive decline over a 1-year period in very old frail institutionalized subjects. The aim of the present analysis was to assess the role of hemodynamic parameters such as blood pressure (BP), heart rate (HR), cfPWV and central/peripheral Pulse Pressure Amplification (PPA) on cognitive decline over a period of 2 years in very old frail subjects. Design and method: 682 subjects from the PARTAGE study cohort, aged >80 years (mean age at inclusion: 87.5 ± 5 y) and living in French and Italian nursing homes, were analyzed. MMSE score was assessed at baseline (BL) and at the end of the first and second year of follow-up (2y-FU). Subjects with a decrease in MMSE of >=3 points between BL and 2y-FU were considered as "decliners". cfPWV and PPA at baseline were assessed with an arterial tonometer. Results: After adjustment for baseline MMSE, HR, BMI, age, education level and ADL, cfPWV was higher and PPA lower in "decliners" compared to "non-decliners, while BP did not differ between the 2 groups. Logistic multivariate analysis also revealed that high cfPWV, low PPA, high HR and low ADL were all determinants of MMSE decline. (Figure: Analysis of baseline factors associated with "decliners" status using multiple logistic regression model). Figure. No caption available. Conclusions: This 2-year longitudinal study in very old institutionalized individuals shows that arterial stiffness and high heart rate enabled to identify subjects at higher risk of cognitive decline, while blood pressure alone did not appear to have a significant predictive value. These findings highlight the contribution of vascular determinants in cognitive decline even in this very old population.